Virtual determination of sex: Estimating cut off value of digital metric traits of foramen magnum on three-dimensional computed tomography with receiver operating characteristic and logistic regression analysis - Harish Kumar S Agarwal; Pardaman Singh Setia; Suryamani Pandey (Wolters Kluwer Medknow Publications, 2021)
Background: Radiological imaging plays a pivotal role in forensic anthropology. As have the imaging techniques advances, so have the digital skeletal measurements inched towards precision. Secular trends of the population keep on changing in modern times. Hence, finding the precise technique of bone measurement, with greater reproducibility, in modern population is always needed in making population specific biological profile. Aim and Objective: The aim of this study was to estimate the accuracy of the foramen magnum measurement, obtained by three dimensional multi-detector computed tomography using volume rendering technique with the cut off value of each variable, in sex determination of an individual. Materials and Methods: Two metric traits, an antero-posterior diameter (APD) and transverse diameter (TD), were measured digitally in an analysis of 130 radiological images having equal proportion of male and female samples. Foramen magnum index and area of foramen magnum (Area by Radinsky's [AR], Area by Teixeira's [AT]) were derived from APD and TD. Results: Descriptive statistical analysis, using unpaired t-test, showed significant higher value in males in all the variables. Using Pearson correlation analysis, maximum correlation was observed between area (AT and AR r = 0.999) and between area and TD (AR r = 0.955 and AT r = 0.945 respectively). When used individually, TD had the highest predictive value (67.7%) for sex determination among all the parameters followed by AT (65.4%) and AR (64.6%). Cutoff value of variables TD,AR and AT were 29.9 mm, 841.80 mm2 and 849.70 mm2 respectively. Receiver operating characteristic curve predicted male and female sex with 96.2% and 89.2% accuracy respectively. The overall accuracy of the model was 92.7%. Conclusion: Measurements from 3D CT using volume rendering technique were precise, and the application of logistic regression analysis predicted the sex with more accuracy.